High‐Temperature Strain Localization and the Nucleation of Oceanic Core Complexes (16.5°N, Mid‐Atlantic Ridge). Issue 9 (14th September 2021) - Casini, Leonardo; Maino, Matteo; Sanfilippo, Alessio; Ildefonse, Benoit; Dick, Henry J. B.
Abstract: Extension at slow to ultraslow midoceanic ridges is mostly accommodated by large detachment faults that expose mantle peridotite and/or lower‐crustal rocks forming Oceanic Core Complexes (OCC). It is commonly accepted that OCC at slow spreading ridges form during the early stage of crystallization of the magmatic crust, when rocks are still close to their solidus temperature. This observation poses significant problems, as nucleation of detachment faults requires significant weakening, which instead is more easily obtained at low temperature. The RV Knorr cruise 210 Leg 5 on the 16.5°N OCC of the Mid‐Atlantic Ridge recovered a narrow shear zone from the plutonic footwall of a mature detachment fault. Troctolites preserve a continuous transition from proto‐mylonite to mylonite and ultra‐mylonite equilibrated at temperature between 1100° and 900°C. EBSD analysis highlights increased phase mixing and weaker crystallographic fabrics in the ultra‐mylonite with respect the mylonitic domains. While host troctolites were completely solidified at the deformation incoming, high‐strain zones preserve evidences of syn‐kinematic melt‐related textures. Fabric patterns combined with plagioclase and olivine grain size piezometry and 1D rheological modeling indicate that the development of ultra‐mylonite requires a switch from dislocation creep to melt‐enhanced grain‐boundary sliding. Activation of this mechanism was promoted by the occurrence of hydrous melt possibly produced by selective re‐melting of plagioclase + Ti‐pargasite microdomains in response to strain localization at subseismic strain rates. This study highlights the importance of hydrated magmatic phases to promote the onset of detachment faulting in OCC. Plain Language Summary: Midoceanic ridges expose the deepest part of the crust and the mantle in dome‐like structures called Oceanic Core Complexes. These structures form by extreme crustal extension accommodated by large faults, soon after crystallization of the magmatic crust. This observation rises significant problems, as high temperatures generally promote ductile deformation of the rocks, not faulting and brittle deformation. The RV Knorr cruise 210 Leg 5 on the 16.5°N OCC of the Mid‐Atlantic Ridge recovered a mature fault zone deforming mafic rocks defined as amphibole‐bearing troctolite. The rocks show a gradient of deformation marked by a progressive decrease of grain size and increasing mixing of different minerals, which become maximum in a narrow 1‐cm‐thick band. Numerical simulations successfully replicate the microstructure observed in the most deformed zone only assuming very high velocity close to seismic rates. We argue that the presence of a small fraction of intergranular melt derived from selective melting of amphibole and plagioclase served as tectonic lubricant promoting fast deformation and localization at high temperature. The results of this study highlights the importance of amphibole, and possibly other hydrated magmatic minerals, to localize deformation, ultimately yielding to crustal extension and formation of the oceans. Key Points: Troctolites dredged from a detachment fault at the Mid Atlantic Ridge, 16°N preserve a narrow HT shear zone Localization at high temperature close to solidus conditions is accommodated by switching from dislocation creep to Grain Boundary Sliding Selective remelting of magmatic amphibole triggers Grain Boundary Sliding